The Influence of the Service Quality dimension on Attitudinal Loyalty and Behavioral Loyalty moderated by the Level of Internet Usage and switching costs study case on Indihome in Indonesia: Study Case on Indihome in Indonesia - Teguh Widodo; Rifqi Jauhari (Pusat Penelitian dan Pengabdian Pada Masyarakat (P3M) STIE Pasundan, 2023)
Although the number of Indihome users climbed, the company's fixed broadband market share fell. Data on poor customer loyalty behavior and a negative attitude toward customer loyalty reinforce the suspicion that there is a decline in Indihome customer loyalty. To research the factors contributing to declining loyalty, this study employs the Service Quality internet service provider model. Its independent variables include Network Quality, Customer Service, Information Quality, and Security. The dependent variables examined in this study are Attitudinal Loyalty and Behavioral Loyalty. The moderator variables examined in this study are Internet Usage Level and Switching Cost. The eight variables' causal links create a structural equation model (SEM). Data were collected from 408 Indihome internet users, and WarpPLS 8.0 software was used to analyze the data. This study's findings suggest that to retain clients, and a supplier must continue offering comprehensive, current, practical, and accurate information. They must also be mindful of the importance of fostering client loyalty so customers can continue subscribing. Additionally, they must intensify efforts to improve customer support for Internet customers. Finally, because it can reduce Attitudinal Loyalty, the supplier needs to Strengthen Security, which has a high Switching Cost.